Intrahousehold allocation of household production: A comparative analysis for Sub-Saharan African countries - Fernando Rios-Avila; Abena D. Oduro; Luiza Nassif Pires (Levy Economics Institute of Bard College, 2021)
In this working paper, we analyze factors that may explain gender differences in the allocation of time to household production in sub-Saharan Africa. The study uses time use survey data to analyze the determinants of time spent on household production by husbands and wives in nuclear families in Ethiopia, Ghana, Tanzania, and South Africa. We assume that the time spent by each spouse is a function of personal and household characteristics. A bivariate Tobit model is used to estimate the marginal impact of a set of key variables that figure recurrently in the literature on time allocation. We observe a high degree of variability in the results for the set of countries, which does not allow us to draw hard general conclusions. We do find some weak evidence that supports time availability and gender ideology theory as well as for the hypothesis that bargaining power plays a role in explaining the intrahousehold allocation of household production.
Keywords: D13; D61; J22; C34; 330; Time Use; Household Production; Economics of the Family; Gender